Reason and responsibility reading Rizal’s letter to his Maloleña compatriots using the capabilities approach. - Durano, Marina B. (2011)
Rizal’s letter to the women of Malolos emphasized reason and supported the education of women so that they may be enlightened, religiousness required reason, without reason there was only religiosity. Rizal’s letter argued that women’s value was contingent on their contribution to the Filipino identity, stressing how the character of motherhood reflected the character of motherland. Sen and Nussbaum’s capabilities approach is a broad framework within the liberal tradition followed by Rizal that allows for a better appreciation of Rizal’s messages in the context of modern-day understandings of development. In particular, reason and affiliation are central to the capabilities approach, which regards women (and men) as bearers of intrinsic value, helping identify not only the potential but also the limits of Rizal’s arguments. Current debates pertaining to individual rights and choice, including those on reproductive rights, provide a platform on which the relevance of Rizal’s messages may be tested. It is shown that the capabilities approach enhances Rizal’s messages for human development.